An infant burial from late pre-Islamic Mleiha (Sharjah, UAE) (poster) - Kutterer, Adelina; Jasim, Sabah A. (Proceedings of the Seminar for Arabian Studies, 2013)
An infant skeleton discovered in the late pre-Islamic settlement area at Mleiha (Sharjah, UAE) is an exceptional finding at this site, where all excavated grave buildings were devoid of preserved human skeletons. The remains of the baby yielded evidence for pathological processes, possibly leading to its untimely death. A radiocarbon date and the typology of a carnelian bead provide good chronological evidence for contemporaneity of the burial and the surrounding domestic structures. As no collagen is preserved in the bones, little can be deduced with regard to the nutritional status of the baby, but carbon and oxygen isotopie ratios obtained from bone apatite were documented.